2017
DOI: 10.1177/0897190017743132
|View full text |Cite
|
Sign up to set email alerts
|

Time–Motion Analysis of Nurses Utilizing Insulin Pen Devices Compared to Vial and Syringe in an Inpatient Setting

Abstract: The time taken by nurses to prepare and administer insulin was lower with the pen device compared with vial and syringe. Furthermore, areas were identified for potential nursing education to enhance safe and appropriate use of insulin with both delivery methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…This results in younger and less experienced nurses in the healthcare system of Nepal. Similar cases of insufficient knowledge of practicing nurses on insulin administration were observed in Northern Ireland [ 9 ], Pakistan [ 11 ], Greece [ 12 ], and United States [ 30 ]. Other studies in Jordan [ 10 ] and United States [ 31 ] also reported that nurses had inadequate knowledge on insulin.…”
Section: Discussionmentioning
confidence: 55%
“…This results in younger and less experienced nurses in the healthcare system of Nepal. Similar cases of insufficient knowledge of practicing nurses on insulin administration were observed in Northern Ireland [ 9 ], Pakistan [ 11 ], Greece [ 12 ], and United States [ 30 ]. Other studies in Jordan [ 10 ] and United States [ 31 ] also reported that nurses had inadequate knowledge on insulin.…”
Section: Discussionmentioning
confidence: 55%